Deep analysis of Raman spectra of ZnO:Mo and ZnO:In sprayed thin films along with LO and TA+LO bands investigation. (April 2016) - Souissi, A.; Amlouk, M.; Khemakhem, H.; Guermazi, S.
Abstract: ZnO and Mo, In doped ZnO thin films with the molar ratios (Mo/Zn) and (In/Zn) were dosed at 1%, 2% and 3%, respectively. These films were deposited on amorphous SiO2 substrate at 460 °C by the spray-pyrolysis process. A useful and concise reminder of the spatial resolutions of Raman spectroscopy was presented. The vibrational responses of these films at high doping exhibited strong fluctuations that were resolved by successive digital processing, choice of the optimal profile of the baseline, suppression of fluorescence and/or photoluminescence, and noise reduction. These treated spectra have allowed to identify possible multi-modes in highly doped studied samples and revealed the presence of LO and TA+LO broad bands, whose second was at cascade and could be explored in optoelectronic and sensitive systems. Highlights: Choice of good Raman parameters for quality spectra. Thorough analysis of spectra using an appropriate numerical processing. Highlighting of Raman multimode coming from different processes. TA+LO cascade phenomenon observed at high doping from 80.7 to 87.6/1.7 meV. Possible exploitation of these samples for optoelectronic and sensitive devices.